Strategi kepala sekolah menengah dalam mengelola perilaku interpersonal dan kelompok melalui pendekatan kepemimpinan situasional - Hutabian, Edwin; Yoserizal, Yoserizal; Hadiyanto, Hadiyanto; Nellitawati, Nellitawati; Kadri, Hanif Al (Journal of Educational Administration and Leadership, 2025)
Abstract This study aims to examine the strategies used by high school (SMA/SMK) principals in managing interpersonal and group behavior through a situational leadership approach. The review was conducted using the Systematic Literature Review (SLR) method, analyzing eleven relevant studies from various countries, including Indonesia, that discuss the implementation of situational leadership styles in the context of secondary education. The findings indicate that principals who apply situational leadership are able to adapt their leadership style based on teachers' readiness levels, school environmental conditions, and the dynamics of work groups. This approach has a significant positive impact on teacher motivation, team collaboration, behavior management, and student learning outcomes. Furthermore, the study found that an adaptive combination of transformational, transactional, and situational leadership styles can enhance leadership effectiveness. Therefore, situational leadership strategies serve as an important framework for principals in creating a supportive and competitive learning environment.